Moderate Morality: An Interest-Based Contractarian Defense & its Applied Result in the Political Ethics of International Relations - Shirzad Peik Herfeh (Journal of Philosophical Investigations, 2017)
What is morality’s scope? Should all our actions be evaluated morally? Is it necessary to be causally responsible for harm to have a responsibility to reduce it? Is there a morally relevant distinction between those consequences of our actions which we intend or do and those which we foresee but do not intend or allow but do not do? Is helping others a matter of supererogation (i.e. beyond the call of moral duty) or a matter of obligation? These are crucial questions that need to be debated in normative and applied ethics. However, they were not raised seriously and independently until the last decades of the 20th century. There are several answers to these questions. This paper defends the answers of an approach which is called “moderate morality.” So, at first, it defines “moderate morality,” and pays heed to the views of its opponents, including Peter Singer, Shelly Kagan, and Peter Unger. Then, it tries to defend “moderate morality” based on “interest-based contractarianism.” Finally, it examines “its result in applied ethics” and tries to find a reasonable answer to a crucial question in the “political ethics of international relations” in our globalized era: What moral obligation, if any, do we have individually and as a society toward the people whose basic human rights are being violated not only in our country but also all over the world?